Study of the Relationship between Job Satisfaction and Work Performance of Personnel in the Industrial Sector - สาพิมพ์, เกศกนก; เสมศรี, ศุภโชค; โตท่าโรง, เพียร; ใจดีเจตจอหอ, สิทธิกร (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to 1. Study the happiness of working in industrial personnel 2. Study the efficiency of working in industrial personnel 3. Study the relationship between happiness of working and efficiency of working in industrial personnel by the population and sample group, namely, 400 industrial personnel in Lat Krabang District, Bangkok. Simple random sampling was used. A questionnaire was used as the research tool. There were 3 parts: personal factors, happiness of working in work, and efficiency of working in work, which were found to be content consistent by experts. The questionnaire had a reliability value of .819. The statistics used in the study were percentage, mean, standard deviation, comparison of differences between 2 variables (Independent-Samples t-test), comparison of differences between more than 2 variables using One-way Analysis of Variance (One-way Anova), and Pearson Correlation. The research results on personal factors found that The majority of the sample was female, 50.4 percent, aged 26-30 years, 42.1 percent had a bachelor's degree, 37.6 percent had worked for 3 years or more, 37.1 percent had a monthly income of 15,001-20,000 baht, 48.6 percent had an operational level job, 76.9 percent. Overall, happiness at work was at a high level (4.27), and overall work efficiency was at a high level (4.38). The results of the test of hypothesis 1 found that personal factors such as gender, age, and education were different, resulting in different work efficiency. In terms of working age, average monthly income, and job position, there was no difference in work efficiency. Hypothesis 2: Happiness at work was related to work efficiency, with a moderate relationship (0.671**) with statistical significance at the 0.01 level.